Global knowledge-power asymmetries and student mental health in sub-Saharan Africa: A case study from South Africa - Bantjes, Jason (Journal of International Students, 2023)
In the past decade concern about the mental health of university students has been growing worldwide. Yet epidemiological data and intervention research on student mental health comes predominantly from high income western countries in the Global North, with a relative scarcity of studies from sub-Saharan Africa and other countries in the Global South. While universities in the Global North and Global South face similar challenges to provide accessible, acceptable, and effective mental health services to students, there are also important historical, cultural, economic, and political issues that make it necessary for context-sensitive research which is responsive to the needs of students in the Global South. Using South Africa (SA) as a case study, this commentary aims to explore the relevance and appropriateness of uncritically importing knowledge and “evidence-based” strategies to student mental health challenges from the Global North into sub-Saharan Africa.